Pengaruh Gaya Kepemimpinan dan Beban Kerja Terhadap Kinerja Pegawai Melalui Motivasi Sebagai Variabel Intervening pada Puskesmas Malalak - Zhiana Efendi; M. Afuan; Deni Saputra (CV. ITTC INDONESIA, 2026)
This study aims to examine and analyze the effect of leadership style and workload on employee performance through motivation as an intervening variable at Malalak Public Health Center. The population of this study consisted of all employees of Malalak Public Health Center, with a saturated sampling technique used as the sampling method. Data were collected through questionnaire distribution and analyzed using path analysis with the support of statistical software. This research applied a Structural Equation Modeling (SEM) approach using SmartPLS 3.0 as the analysis tool. The results indicate that leadership style has a significant effect on employee performance, while workload has no significant effect on employee performance. Leadership style has a significant effect on motivation, and workload also has a significant effect on motivation. However, motivation does not have a significant effect on employee performance. Furthermore, motivation does not mediate the relationship between leadership style and employee performance, nor does it mediate the relationship between workload and employee performance